Photosystem I, when excited in the chlorophyll Qy absorption band, feeds on negative entropy - Jennings, Robert C; Belgio, Erica; Zucchelli, Giuseppe (Biophysical chemistry, 2018)
It is often suggested that Life may lay outside the normal laws of Physics and particularly of Thermodynamics, though this point of view is refuted by many. As the Living State may be thought of as an open system, often far from equilibrium, most attempts at placing Life under the umbrella of the laws of Physics have been based, particularly in recent years, on non-equilibrium Thermodynamics and particularly the Maximum Entropy Production Principle. In this view it is the dissipation of entropy (heat) which permits the ever increasing complexity of Living Systems in biological evolution and the maintenance of this complexity. However, these studies usually consider such biological entities as whole cells, organs, whole organisms and even Life itself at the entire terrestrial level. This requires making assumptions concerning the Living State, which are often not soundly based on observation and lack a defined model structure. The present study is based on an entirely different approach, in which a classical thermodynamic analysis of a well-defined biological nanoparticle, plant Photosystem I, is performed. This photosynthetic structure, which absorbs light and performs primary and secondary charge separation, operates with a quantum efficiency close to one. It is demonstrated that when monochromatic light is absorbed by the lowest lying electronic transition, the chlorophyll Qy transition, entropy production in the system bath plus entropy changes internal to the system are numerically less than the entropy decrease of the light field. A Second Law violation is therefore suggested for these experimental conditions. This conclusion, while at first sight is supportive of the famous and much discussed statement of Schroedinger, that "Life feeds on negentropy", is analysed and the conditions in which this statement may be considered valid for a Plant Photosystem are defined and delimited. The remarkably high quantum efficiency, leading to minimal entropy production (energy wastage), seems to suggest that evolution of Photosystem I has gone down the road of maximal energy efficiency as distinct from maximal entropy production. Photosystem I cannot be considered a maximum entropy dissipation structure.
Keywords: entropie; Photosystem II Protein Complex; Chlorophyll; Entropy and primary photosynthetic processes; Entropy balance; chlorofyl; fyziologická absorpce; Maximal energy efficiency plant photosystem I; Entropy; Photosystem I Protein Complex; Schroedinger's neg-entropy; fotosystém I (proteinový komplex); Absorption, Physiological; fotosystém II (proteinový komplex)